Short Body Height and Pre-pregnancy Overweight for Increased Risk of Gestational Diabetes Mellitus: A Population-Based Cohort Study - Li, Jing; Wang, Peng; Zhang, Cuiping; Leng, Junhong; Li, Nan; Wang, Leishen; Li, Wei; Liu, Huikun; Yu, Zhijie; Hu, Gang; Chan, Juliana C. N.; Yang, Xilin (Frontiers in Endocrinology, 2018)
Background: Short height is associated with gestational diabetes mellitus (GDM) but the underlying mechanism remains unknown. This study aimed to explore whether short height has a synergistic effect with pre-pregnancy overweight/obesity and undue weight gain on the risk of GDM. Methods: We recruited 19,962 singleton pregnant women from their first antenatal care visit in urban Tianjin, China, between October 2010 to August 2012. At 24-28 weeks of gestation, women underwent a 50-gram 1-hour glucose challenge test followed by a 75-gram 2-hour oral glucose tolerance test if the GCT result was ≥7.8 mmol/L. GDM was defined by the International Association of Diabetes and Pregnancy Study Group’s cut-points. Univariable and multivariable logistic regression analyses were performed to obtain odds ratios (ORs) and 95% confidence intervals (CIs). Restricted cubic spline analysis nested in the logistic regression analysis was used to identify a cutoff point of height for GDM. Additive interaction was used to test interactions between short height, pregnancy overweight and undue weight gain. Results: A total of 1,517 (or 7.6%) women developed GDM. The risk of GDM increased rapidly with a decreasing height from 158 cm and downwards. Using height ≥158 cm as the reference group, women with <158 cm of height were at increased GDM risk (adjusted OR: 1.44, 95%CI: 1.18-1.75). Maternal overweight/obesity at the first antenatal care visit greatly enhanced the OR of short height for GDM (adjusted OR: 3.78, 95%CI: 2.84-5.03) with significant additive interaction (P<0.05). However, the interaction between short height and undue weight gain was non-significant (P>0.05). Conclusions: In Chinese pregnant women in urban Tianjin, height <158 cm had a synergistic effect with pre-pregnancy overweight on the risk of GDM.